Fostering Sustainable Manufacturing in Africa: A Sustainable Supply Chain Management Framework for a Green Future - Ahmed Idi Kato; Ntise Hendrick Manchidi (Administrative Sciences)
Sustainable Supply Chain Management (SSCM) emerges as a vital catalyst for inclusive growth and sustainable development, particularly in emerging economies where the manufacturing sector is central to economic progress. This study offers an in-depth analysis of the current research landscape on SSCM in the context of developing nations, outlining key theoretical frameworks and advocating for a solid conceptual foundation alongside a structured agenda for future research initiatives. This study employs a structured literature review technique to analyze 92 published articles indexed by Scopus from 2013 to 2024, revealing a burgeoning trend in the subject of global supply chains in developing nations. The analysis identifies key keywords such as “sustainable supply chain management,” “manufacturing industries,” “inclusive growth,” and “supply chain and sustainability,” and develops a conceptual model that elucidates how SSCM practices can be effectively integrated into manufacturing sectors to facilitate equitable growth and enhance business competitiveness. This work’s novelty lies in employing a systematic literature review to develop a holistic SSCM conceptual framework constructed upon six primary drivers: business model innovation, inclusive SSCM, corporate governance and leadership, technological and innovation capabilities, policy and regulatory environment, and circular feedback. This model addresses the ambiguity surrounding SSCM and inclusive growth, providing a robust foundation for future research and performance measurement. This study contributes to the field by providing a practical and theoretically grounded framework for researchers, policymakers, and practitioners seeking to implement impactful and effective SSCM initiatives in developing nations’ manufacturing sectors to promote inclusive growth and sustainable development.